PHRASEOLOGICAL UNITS CONTAINING NAMES OF PARTS OF THE HUMAN BODY IN THE QUECHUA FROM AYACUCHO - Gálvez Astorayme, Isabel (2013)
This paper deals with a particular kind of phraseological units present in thespeech of the Quechua-speaking users of the dialect of Ayacucho: nominal and verbal locutions of the human body (somatisms). The analysis of these units is focusedon the description and explanation of the cultural context that motivates themeaning these expressions show in the Andean mentality. Thus, it is postulatedthat the Quechua language and culture are decisive, both as a system and Andeanmentality, for the resemantization of such units.